Perbandingan Biaya dan Waktu Pekerjaan Pondasi Bore Pile dan Spun Pile - Dabukke, Oktavia; Wacono, Sidiq (Media Komunikasi Dunia Ilmu Sipil (MoDuluS), 2024)
Decision-making on the work methods used in a construction project is very important. As is the case in selecting the foundation work method to be used because the foundation has a very important role in carrying out substructure work. Choosing the right foundation work implementation method will expedite the work process so it is necessary to know how much cost and time is needed to carry out each foundation work. The purpose of this study is to find out how much the comparison of costs and time is required in carrying out bore pile and spun pile foundation work. The data needed to calculate costs and time for the two foundation work methods include the volume of work, the multiplier coefficient which refers to the Decree of the Minister of PUPR No. 1 of 2022, data on workforce, equipment, as well as the duration and method of carrying out the required work. Based on the researcher's analysis conducted by comparing the implementation of the two foundation work methods, namely using the bore pile and spun pile, the total cost of implementing the bore pile foundation work is Rp. 13,405,153,637 with an execution time of 189 days. Meanwhile, if you use a spun pile foundation, the cost is Rp. 11,590,475,275 with an execution time of 173 days. So that the two methods of carrying out the foundation work have a cost difference of Rp. 1,814,678,362 and a difference of 16 days.